To understand how to differentiate composite functions using the Chain Rule, we first need to know what a composite function is.
A composite function is made by combining two functions. We can write it as ( f(g(x)) ), where ( f ) is one function and ( g ) is another.
The Chain Rule helps us find the derivative (or the rate of change) of this composite function. Here’s how it works:
Here’s the formula for the Chain Rule:
[ \frac{d}{dx}[f(g(x))] = f'(g(x)) \cdot g'(x) ]
Now, let's look at an example. Imagine we have the function ( h(x) = (3x + 2)^4 ).
In this case:
Now, let's go through the steps:
Differentiate the outer function:
The derivative is ( f'(u) = 4u^3 ).
So when we substitute back in, we have ( f'(g(x)) = 4(3x + 2)^3 ).
Differentiate the inner function:
The derivative is ( g'(x) = 3 ).
Now, let’s put it all together:
[ h'(x) = f'(g(x)) \cdot g'(x) = 4(3x + 2)^3 \cdot 3 = 12(3x + 2)^3 ]
And that’s how you use the Chain Rule!
To understand how to differentiate composite functions using the Chain Rule, we first need to know what a composite function is.
A composite function is made by combining two functions. We can write it as ( f(g(x)) ), where ( f ) is one function and ( g ) is another.
The Chain Rule helps us find the derivative (or the rate of change) of this composite function. Here’s how it works:
Here’s the formula for the Chain Rule:
[ \frac{d}{dx}[f(g(x))] = f'(g(x)) \cdot g'(x) ]
Now, let's look at an example. Imagine we have the function ( h(x) = (3x + 2)^4 ).
In this case:
Now, let's go through the steps:
Differentiate the outer function:
The derivative is ( f'(u) = 4u^3 ).
So when we substitute back in, we have ( f'(g(x)) = 4(3x + 2)^3 ).
Differentiate the inner function:
The derivative is ( g'(x) = 3 ).
Now, let’s put it all together:
[ h'(x) = f'(g(x)) \cdot g'(x) = 4(3x + 2)^3 \cdot 3 = 12(3x + 2)^3 ]
And that’s how you use the Chain Rule!